Large-area regular periodic surface structures on 4H-SiC induced by defocused femtosecond laser. (1st September 2022) - He, Ziyu; Xie, Xiaozhu; Long, Jiangyou; Liu, Tao; Zhang, Zucheng; Lai, Qing
Abstract: Femtosecond (fs) laser has been proved to induce periodic surface structure formation with various periods. Previous studies employed complex optical means and specific processing environments to induce nano-sized periodic surface structures. In this study, a defocused fs laser was utilized to realize a high-stability and straightforward method for generating periodic structures on silicon carbide (SiC) surfaces. Due to its more uniform energy distribution, the defocused laser effectively attenuates the unstable fluid flow caused by the Marangoni convection, thereby improving the consistency of laser- induced periodic surface structure morphology and size. The effects of laser processing parameters on the ripple period, density, and morphology were systematically investigated. Moreover, an appropriate physical process was adopted to explain the formation of the nanostructures. A high laser pulse number was considered the key to forming large-area dense nanoripples, which possessed a smooth edge profile and similar period. Under optimal parameters, large-area regular nanoripples with periods of ∼100 nm could be induced on the SiC surface by a defocused fs laser method. Meanwhile, a two-step laser-inducing method was proposed to fabricate an array of two-dimensional square-shaped nanocolumns with a size of 60 nm × 60 nm. The two-step laser-inducing method realized tuning in the surface nanostructure morphology and localized nanostructures rewriting by adjusting the laser processing parameters. This large-area periodic structure inducing method showed the possibility of making laser-writing technology to be flexible, straightforward and, hence, competitive for advanced industrial application based on surface nanostructuring.